Analisis dan Perancangan Website Pembelajaran Bahasa Secara Mandiri di Self Access Language Learning Center Bina Nusantara - Pranoto, Hady (Bina Nusantara University, 2010)
The purpose of this research is to build an independent language learning applications using Internet technologies to facilitate the user in learning the language. The research method used is by analyzing the ongoing learning process; analyze the constraints and limitations of existing facilities and designing new processes to address existing constraints and limitations. In designing a language self learning website authors examine the existing through observation, interviews and questionnaires to the stakeholders who use the system. Observations also observed duration of the user in conducting learning activities, and provided space to accommodate the transaction. After analysis of the current system, author designing the new system using object-oriented design methods and using analysis tools UML. After completed the system design done system built using ASP.NET programming language. The Conclusions is an independent language learning applications using Internet technology giving easy way to facilitate the learning process in terms of accesing time and place, and the application also provide facilities for teacher to monitoring student self learning.